e-LIT: Pengembangan Instrumen Penilaian Literasi Digital bagi Generasi Digital-Native - Karitas, Chionia; Suwartono, Christiany (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Digital literacy is becoming increasingly important in the current era of digitalization, but the level of digital literacy in Indonesia is still low. This research aims to develop and test the psychometric properties of the LD-UAJ Digital Literacy Test as a measure of students' digital literacy abilities. The LD-UAJ test is designed to measure the minimum proficiency in digital technology before entering the workforce. It is an achievement test consisting of 30 multiple-choice questions that measure five dimensions of digital literacy: information and data literacy, communication and collaboration, digital competence, security, and problem-solving. The development of the LD-UAJ digital literacy test involved two data collection phases with 97 active undergraduate students. Through the convenience sampling technique, 46 participants were involved in the pilot test, and 51 in the field test. In this study, item analysis, validity, and reliability methods were used to evaluate the psychometric properties of the LD-UAJ test. The analysis results show that the LD-UAJ test has good validity in terms of content validity, particularly through expert opinions, and face validity with the participants. The reliability results indicate that the LD-UAJ test is reliable with an omega coefficient of 0.82. Further research is needed to validate the criterion-related validity as the criteria used during the development did not show a strong relationship with digital literacy. This study also highlights the existing barriers in the development of the LD-UAJ test, such as time limitations, low student interest and participation, and difficulties in obtaining a sufficiently large sample. However, the LD-UAJ test is expected to be a useful measuring tool in evaluating students' level of digital literacy and can help recommend appropriate training to enhance their digital literacy understanding. Keywords: